SISTEM INFORMASI KEANGGOTAAN KELUARGA WAYA SURATIRTA MENGGUNAKAN METODE KNUTH MORRIS PRATT (KMP) BERBASIS WEB MOBILE - Pratama, Fandi; Husni Al Amin, Imam (Information Technology and Telematics, 2018)
ABSTRACT Membership system is a system for managing data within an organization, institution, or company. The family as one of the small organizations that manage their members in this case the Family Waya Suratirta Pemalang District. Good data management is needed as an important point in processing the data so that data retrieval can be easily done. By implementing Knuth Morris Pratt (KMP) algorithm, this research has resulted in membership information system that can facilitate the management of member data and speed up data search so that time of data collection becomes more effective and reduce paper usage, because it has been made online and mobile web based.